The time keeper - Albom, Mitch, 1958- (London : Sphere, 2013)
Following his punishment for trying to measure God's greatest gift, Father Time is granted his freedom and is sent on a mission to redeem himself by teaching two earthly people the true meaning of time.
Adult.
Adult
Keywords: Time -- Fiction; Time -- Fiction; Fantastic fiction; Fantastic fiction